Pengaruh Indeks Pembangunan Manusia, Konsumsi Energi, dan Kepadatan Penduduk terhadap Indeks Kualitas Lingkungan Hidup dalam Perspektif Sustainable Development Goals (SDGs) di Provinsi Indonesia Tahun 2015-2024 - Camila Nurhaliza; Siti Nurjanah; Tuty Sariwulan (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of the Human Development Index (HDI), energy consumption, and population density on the Environmental Quality Index (EQI) in 34 provinces of Indonesia during the 2015-2024 period from the perspective of Sustainable Development Goals (SDGs). This research uses a quantitative approach with panel data regression analysis using the Fixed Effect Model (FEM). The data used are secondary data obtained from the Central Bureau of Statistics (BPS) and the Ministry of Environment and Forestry (KLHK). The results show that HDI has a positive and significant effect on EQI (t = 2.210; p = 0.034), energy consumption has a positive and significant effect on EQI (t = 2.187; p = 0.036), and population density also has a positive and significant effect on EQI (t = 3.288; p = 0.002). The adjusted R-squared value of 76.76% indicates that the three independent variables are able to explain 76.76% of the variation in EQI. These findings confirm that improving human development, sustainable energy management, and well-managed population density can support environmental quality improvement, thereby contributing to the achievement of SDGs in Indonesia.